2013
DOI: 10.6061/clinics/2013(06)14
|View full text |Cite
|
Sign up to set email alerts
|

Human papillomavirus types 16 and 18 and the prognosis of patients with stage I cervical cancer

Abstract: OBJECTIVE:This study sought to evaluate the prevalence of human papillomavirus (HPV) types 16 and 18 in women with clinical stage IB cervical cancer treated by radical hysterectomy with pelvic lymphadenectomy as well as to establish a correlation between HPV type and cancer prognosis.METHODS:A single-center cohort study was conducted with 86 patients who had undergone radical hysterectomy for stage I cervical cancer. Prognostic factors and the presence of HPV 16 and 18 were analyzed using a polymerase chain re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
21
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 38 publications
2
21
0
2
Order By: Relevance
“…In addition, HPV31-related and HPV58-related types were found to be associated with better survival outcome [7, 8]. However, no prognostic value of HPV type was reported by the other studies [9, 10]. The inconsistency may be attributed to the significant differences in sample size, length of follow-up, assay methods, and adjustment for known prognostic factors.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, HPV31-related and HPV58-related types were found to be associated with better survival outcome [7, 8]. However, no prognostic value of HPV type was reported by the other studies [9, 10]. The inconsistency may be attributed to the significant differences in sample size, length of follow-up, assay methods, and adjustment for known prognostic factors.…”
Section: Introductionmentioning
confidence: 99%
“…High risk (HR)-HPV is the main cause of CC. HR-HPV subtypes such as HPV16, 18, 31, 33, 35, 39, 45, 51, 52, 56, and 59 are closely associated (in decreasing oncogenic potential) with the occurrence of CC, and these associations are seen throughout the world [10], but there are some regional differences in the prevalence of the different HPV subtypes [11,12]. The HR-HPV viral load indicates the activity of HPV-DNA in the body [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…The HR-HPV viral load indicates the activity of HPV-DNA in the body [13,14]. Studies showed that the type of HPV infection is closely related to the severity of cervical lesions and treatment prognosis [10][11][12], but there are inconsistent results from the studies on the correlation between the HPV viral load and the severity of cervical lesions [13][14][15][16][17][18][19]. At present, the correlation between the HPV viral load and cervical lesions has not been determined, and the signi cance of the HPV viral load in the detection and treatment of cervical lesions is still controversial [17,19].…”
Section: Introductionmentioning
confidence: 99%
“…However, some studies showed that HPV DNA did not have any prognostic implication [8,9]. Furthermore, existing results on the relationship of HPV genotype with survival are also heterogeneous [4,10]. Therefore, identifying new molecular targets was needed to improve the prognosis and quality of life of patients with cervical cancer.…”
Section: Introductionmentioning
confidence: 99%
“…The major cause of invasive cervical cancer is persistent infection with high-risk human papillomavirus (HR-HPV). More than 170 genotypes have been described, and 2 HPV species, alpha-7 (HPV 18, 39, 45, 59, 68, and 70) and alpha-9 (HPV 16, 31, 33, 35, 52, 58, and 67), are classified as high-risk geno-DOI: 10.1159/000487434 types due to their high oncogenic potential [4]. Although there has been much evidence on the role of HPV in cervical precursor lesions and invasive cancer, it remains controversial how they affect prognosis of cervical cancer.…”
Section: Introductionmentioning
confidence: 99%